Performance evaluation of ceramic membrane bioreactor: effect of operational parameters on micropollutant removal and membrane fouling - Caglak, Abdulkadir; Chormey, Dotse Selali; Bakirdere, Sezgin; Engin, Guleda Onkal (SPRINGER HEIDELBERG, 2022)
This paper presents the removal of nine potential endocrine disruptors including pesticides, pharmaceuticals and industrial chemicals using a submerged membrane bioreactor (MBR) system. Two lab-scale submerged MBRs having ceramic membranes were operated at three different sludge retention times (SRT: 15, 45, 90 days) and two hydraulic retention times (HRT: 12, 6 h) and the effects of SRT and HRT on both micropollutant removal and membrane fouling were investigated. While the effect of SRT and HRT change was observed on the removal of atrazine, fluoxetine, penconazole, no significant change was detected for the other micropollutants studied. It was determined that physicochemical properties such as distribution coefficient (LogD) and hydrophobicity of micropollutants are also effective on the removal efficiency of micropollutants. High removal efficiencies (>= 97.5%) were observed for hydrophobic pollutants (logD > 3.2) except for penconazole (72.1%) and for hydrophilic pollutants (logD < 3.2) except for atrazine (42.5%). Membrane fouling was significantly affected by different operational parameters applied, with the slowest fouling occurring at 45 days of SRT and 12 h of HRT. However, micropollutant addition did not have a significant effect on membrane fouling. It has been shown that the simultaneous and effective treatment performance for micropollutants makes the membrane bioreactor system a promising wastewater treatment process.
Keywords: Micropollutant; Endocrine disrupting compounds; Membrane bioreactor; Sludge age; Hydraulic retention time; Membrane fouling; ENDOCRINE-DISRUPTING COMPOUNDS; WASTE-WATER TREATMENT; ACTIVATED-SLUDGE PROPERTIES; TREATMENT PLANTS; PHARMACEUTICALS; MBR; FATE; PESTICIDES; BIODEGRADATION; Environmental Sciences & Ecology